Engineering for Rural Development 2019
DOI: 10.22616/erdev2019.18.n032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of operability of maintainable crosspiece

Abstract: Ensuring operability of transport technological machines is connected with increase in characteristics of non-failure operation, durability and maintainability of transmission units, in particular, of drive lines. The analysis of trends of improvement of designs and technological processes of maintenance operation of drive lines shows that designs of joints with maintainable crosspieces and bearing mount assemblies are perspective. Besides, developments of technical solutions on realization of automated mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The value of the diagnostic temperature of the subject of diagnostics taking into account the above facts is determined by the following polynomial [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the diagnostic temperature of the subject of diagnostics taking into account the above facts is determined by the following polynomial [9].…”
Section: Resultsmentioning
confidence: 99%
“…The development of an analytical mathematical model of temperature in the friction zone Θ F , ºC, in relation to the joints of the drive lines is devoted to research [10], and the mathematical model obtained by us earlier takes into account the previously mentioned factors with the exception of the radial play in the CBA (2).…”
Section: Resultsmentioning
confidence: 99%
“…According to [11], tests on agricultural machinery have shown that 14% of mechanical transmission failures are due to universal joints, with about 60% of failures due to cardan joints. According to research [12], the service life of an agricultural cardan shaft is between 5 and 9 years, which is very low considering that it is used only a few days a year. This low service life is influenced by the type of maintenance and use, as well as the conditions of use (terrain, angle of rotation α, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…); insufficient use (cardan shaft).) [12]; improper use (often too long or too short cardan shafts, poorly fixed shafts, too large rotation angles of the joints, application of higher torques than the shaft can withstand [23], etc. ); complex atmospheric conditions [24] (working in rain, wind, dust, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Результаты теоретических исследований были верифицированы, а технология апробирована в условиях стендовых и эксплуатационных испытаний [18][19][20]. Реализация технологии термодиагностики определяется внедрением эффективных методов и средств.…”
unclassified